RELIGIOUS HARMONY INDEX IN SPECIAL REGION OF YOGYAKARTA - Deden Istiawan; Arif Gunawan Santoso; R Rosidin; Ika Safitri Windiarti (Universitas Muhammadiyah Surakarta, 2023)
The existence of the Special Region of Yogyakarta as a city of students, culture, and tourism holds diversity both ethnically, culturally, and religiously; therefore, the Special Region of Yogyakarta is called the city of tolerance. The plurality of the Special Region of Yogyakarta may give rise to conflicts and divisions, including inter-religious conflicts if they are not appropriately managed. One of the successes of developing religious harmony can be assessed by looking at the most basic indicators of harmony at the national and regional levels. This study aims to measure inter-religious harmony in the Special Region of Yogyakarta. Variables that become measuring instruments have three dimensions: tolerance, dimensions, and dimensions of cooperation. The study used quantitative methods with a total sample of 400 respondents spread across Yogyakarta City, Bantul Regency, Kulon Progo Regency, and Gunung Kidul Regency. The research findings show that the index of inter-religious harmony in the Special Region of Yogyakarta is 78.90, or in the high level of religious harmony category. For this reason, maintenance must continue improving to achieve a harmonious, harmonious, and harmonious religious life. Although, in general, it is in a high category, there are still sub-dimensions that need special attention, namely caring for the construction of other places of worship and being president or regional head regardless of religion.